Characterization and microstructural studies of life 5O 8 synthesized by the self propagating high temperature combustion method - Yusof, R.; Fadzil, A.F.M.; Kamarulzaman, N.; Subban, R.H.Y.; Ismail, K.; Othman, N.; Basirun, Wan Jefrey; Bustam, M.A.; Puad, S.A. (Springer Verlag (Germany), 2005)
LiFe 5O 8 was synthesized by the self-propagating high temperature combustion synthesis using lithium acetate and iron acetate as starting materials and glycine as reductant. The reaction was rapid when the ignition temperature was reached and the product was a light and porous mass of solid material. Analysis using X-Ray powder diffraction and SEM revealed the amorphous nature of the LiFe 5O 8 precursor material. From particle size analysis, the precursor material was much less than 100 nm, but increased upon annealing at 650 °C and 900 °C.